Comparative evaluation of adhesion formation of prosthetic meshes after intra-abdominal implantation in wistar rats (2014)
Increasingly biomaterials for the repair of abdominal wall defects are used. The aim of this study was to evaluate adhesion formation of prosthetic meshes after intraabdominal implantation to repair a surgical defect in the anterior abdominal wall. This anatomical defect was repaired by one of the three types of previously sterilized meshes: 1) fibroin 2) fibroin with polyethylene glycol and 3) commercial polypropylene mesh as control. The grip score was significantly higher in the commercial polypropylene mesh. Fibroin is a promising biomaterial for treating defects of the abdominal wall.